Oral anticoagulation and antiplatelets in atrial fibrillation patients after myocardial infarction and coronary intervention - Lamberts, Morten; Gislason, Gunnar H; Olesen, Jonas Bjerring; Kristensen, Søren Lund; Schjerning Olsen, Anne-Marie; Mikkelsen, Anders; Christensen, Christine Benn; Lip, Gregory Y H; Køber, Lars; Torp-Pedersen, Christian; Hansen, Morten Lock (Journal of the American College of Cardiology, 2013)
The purpose of this study was to investigate the risk of thrombosis and bleeding according to multiple antithrombotic treatment regimens in atrial fibrillation (AF) patients after myocardial infarction (MI) or percutaneous coronary intervention (PCI). The optimal antithrombotic treatment strategy is unresolved in patients with multiple indications. A total of 12,165 AF patients hospitalized with MI and/or undergoing PCI between 2001 and 2009 were identified by nationwide registries (60.7% male; mean age 75.6 years). Risk of MI/coronary death, ischemic stroke, and bleeding according to antithrombotic treatment regimen was estimated by Cox regression models. Within 1 year, MI or coronary death, ischemic stroke, and bleeding events occurred in 2,255 patients (18.5%), 680 (5.6%), and 769 (6.3%), respectively. Relative to triple therapy (oral anticoagulation [OAC] plus aspirin plus clopidogrel), no increased risk of recurrent coronary events was seen for OAC plus clopidogrel (hazard ratio [HR]: 0.69, 95% confidence interval [CI]: 0.48 to 1.00), OAC plus aspirin (HR: 0.96, 95% CI: 0.77 to 1.19), or aspirin plus clopidogrel (HR: 1.17, 95% CI: 0.96 to 1.42), but aspirin plus clopidogrel was associated with a higher risk of ischemic stroke (HR: 1.50, 95% CI: 1.03 to 2.20). Also, OAC plus aspirin and aspirin plus clopidogrel were associated with a significant increased risk of all-cause death (HR: 1.52, 95% CI: 1.17 to 1.99 and HR: 1.60, 95% CI: 1.25 to 2.05, respectively). When compared to triple therapy, bleeding risk was nonsignificantly lower for OAC plus clopidogrel (HR: 0.78, 95% CI: 0.55 to 1.12) and significantly lower for OAC plus aspirin and aspirin plus clopidogrel. In real-life AF patients with indication for multiple antithrombotic drugs after MI/PCI, OAC and clopidogrel was equal or better on both benefit and safety outcomes compared to triple therapy.